Penerapan Konsep Pembelajaran Tematik Pada Pelajaran Matematika Sebagai Upaya Meningkatkan Hasil Belajar Siswa - Asliana Asliana (JURNAL GLOBAL EDUKASI, 2017)
Abstract: This study aims to improve the learning outcomes of mathematics through the application of thematic learning concepts with the theme of self. Subjects in this study were students of class I SD Negeri 013848 Gedangan district Pulo Bandring academic year 2016/2017. The result of the learning process after the research applied the concept of thematic learning in Mathematics lesson with Self theme as an effort to improve student learning achievement reaches the average value of 75.21 in cycle I with classical completeness of 75.21%. Learning outcomes in cycle II reached an average score of 85.17 with the percentage of classical learning completeness of 100. Can be concluded through the application of thematic learning concepts with self-theme can improve the results of learning mathematics in students of class I SD Negeri 013848 Gedangan district Pulo Bandring academic year 2016/2017. Keywords: thematic, self Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika melalui penerapan konsep pembelajaran tematik dengan tema diri sendiri. Subjek dalam penelitian ini adalah siswa kelas I SDN 013848 Gedangan kec. Pulo Bandring TP. 2016/2017. Hasil proses belajar setelah penelitian menerapkan konsep pembelajaran tematik pada pelajaran Matematika dengan tema Diri Sendiri sebagai upaya meningkatkan hasil belajar siswa mencapai nilai rata-rata 75,21 pada siklus I dengan ketuntasan klasikal sebesar 75,21%. Hasil belajar pada siklus II mencapai nilai rata-rata 85,17 dengan persentase ketuntasan belajar klasikal sebesar 100. Dapat disimpulkan melalui penerapan konsep pembelajaran tematik dengan tema diri sendiri dapat meningkatkan hasil belajar matematika pada siswa kelas I SDN 013848 Gedangan kec. Pulo Bandring TP. 2016/2017. Kata kunci: tematik, diri sendiri